Respiratory Signal Estimation Using Non-invasive Measurements - Vaitkūnas, M.; Dosinas, A.; Bartkevičius, V.; Daunoras, J. (Elektronika ir Elektrotechnika, 2009)
Non-invasive human respiratory function monitoring system, based on inductive plethysmography method is analyzed. The system is intended to be used as worker’s wearable equipment. It employs inductive sensors made of wavy insulated wire secured on expandable belts that surround human rib cage and abdomen. Various parameters of inductive sensors and their influence on sensitiveness were investigated. Signal demodulation is used to produce respiratory signal from an output signal of oscillator with an inductive sensor in circuit. Both signal processing equipment and signals achieved are discussed. Ill. 8, bibl. 5 (in English; summaries in English, Russian and Lithuanian).